Motor coordination excellence model for 16-18 year old skilled kickboxers - Grakhov, I. A.; Zekrin, F. Kh.; Zebzeev, V. V.; Zekrin, A. F. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to develop and test benefits of a new motor coordination excellence model for the 16-18 year old skilled kickboxers.